Administrators' unintentional sensegiving and system reform outcomes - Lok-Sze Wong (Arizona State University, 2019)
One popular diagnosis for the problem of inequitable educational opportunities is the need for schools and schooling systems to undergo systemic change. While research shows that leadership support is essential for implementing system reforms, critical questions remain about how leaders help shift other's understandings and practices. Employing the theory of sensegiving, this longitudinal, multiple-case study examines how administrators help teachers and other administrators make sense of a system reform during the first two years of implementation. I found that administrator's unintentional sensegiving complicated others' understandings of the new system reform, which complicated implementation. Based on these findings, I introduce the concept of unintentional sensegiving to theorize how leaders can give sense in ways they do not intend, yet have large impacts on how others understand and respond to a reform. Before championing a system reform, leaders deserve opportunities to (a) become familiar with the details of that reform and system reforms in general; (b) carefully study their existing systems, including their local contexts, and consider what dynamics might be created when they implement the new reform; (c) explore how their existing systems could shift to match the design of the system reform; and (d) practice drawing on their wells of knowledge to help others shift their understandings about their practice.